Strategic planning in Non-Governmental Organizations: the case of ATLIMARJOM (Research, Society and Development, 2019)
Brazil's economic and political conditions make it impossible for the government itself to meet all of society's needs, which are exacerbated by the current situation in which resources have become increasingly scarce. In this sense, society is at the forefront of organizing actions for the benefit of the population, preserving human rights and structuring social responsibility. In this context, the non-profit institutions of the Third Sector, Non-Governmental Organizations (NGO's) stand out. The purpose of this article is to discuss the importance of Strategic Planning for the non-governmental organization - NGO, ATLIMARJOM, proposing to review and apply it as a management tool. Methodologically, a qualitative research was conducted with a semi-structured interview in-depth, directly with the institution manager, seeking to know the organizational structure in order to increase the awareness that a change in management strategies is required business. As a result, it was possible to verify how much it is necessary to elaborate an efficient strategic planning so that the confidence of the society, strategic partnerships and profitability allied to the social focus of the NGO can be conquered.